Migrasi dan orang Bugis : penelusuran kehadiran Opu Daeng Rilakka pada abad XVIII di Johor - Kesuma, Ima, Andi, 1964-; Gonggong, Anhar (Yogyakarta : Ombak, 2004)
Mass immigration by Bugis to Johor in the 18th century trying to escape from Dutch colonial in their home land of Makassar; includes history of Opu Daeng Rilakka, a royal Bugis-Makassar
Daftar pustaka: p. 139-144
Keywords: Bugis (Malay people) -- Migrations